ئامڕازەکانی بەجیهانیبوونی کولتور توێژینه‌وه‌یه‌كی تیۆریی شیكارییه‌ ئه‌م توێژینه‌وه‌یه‌ به‌شێكه‌ له‌ توێژینه‌وه‌ی نامه‌ی دكتۆرای توێژەر (بحث مستل)‌ - مجید, پەیمان عبدالقادر; عبداەلل, کوێستان علی (Sulaimani Journal for Humanities, 2022)
The permanence of life and the construction of the earth obliged human to practice in the daily life a set of laws and customs and abide by them. These laws and customs are often known as the culture of the community. The culture of society differs from time to time and from one region to another, especially if the times and regions diverge from each other, the difference is much wider and clearer. On the other hand, the overlap of cultures sometimes leads to a kind of merging and mixing of different cultures with each other. From this point of view, we see that the issue of globalization of culture has become one of the common issues among the pioneers of social sciences in general and sociology in particular in this era. This question did not come from a vacuum. Rather, there is a set of civilized and human mechanisms that lead to the emergence of this situation. As these mechanisms affect the emergence of the globalization of culture at the same time have an impact on the cultural identity of society. This research deals with some of these mechanisms in the manner of descriptive-analytic theory and the impact of these mechanisms on cultural identity.